2019
DOI: 10.1177/1753193419886777
|View full text |Cite
|
Sign up to set email alerts
|

Selective denervation of the wrist for chronic pain: a systematic literature review

Abstract: Selective denervation of sensory nerve branches to the wrist is a palliative surgical treatment option for patients with chronic wrist pain when preserving the range of motion and function is preferred. Treatment varies from partial isolated denervation of the posterior interosseous nerve to extensive ‘complete’ denervations. This study aimed to provide an overview of the literature regarding treatment outcomes in the domains of pain, grip strength, patient satisfaction and return to work. MEDLINE (PubMed), EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Among the 81 patients, 59 were reviewed with a minimum of 5 years of follow-up, 4 died, and 18 (22%) could not be reviewed after 5 years and were considered lost to followup. The clinical and radiological analyses were performed on 59 patients (63 procedures) with a mean follow-up of 7.0 AE 1.5 years (5)(6)(7)(8)(9)(10)(11). Comparison of data at 2 years and at the last follow-up was also performed on these same patients.…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 81 patients, 59 were reviewed with a minimum of 5 years of follow-up, 4 died, and 18 (22%) could not be reviewed after 5 years and were considered lost to followup. The clinical and radiological analyses were performed on 59 patients (63 procedures) with a mean follow-up of 7.0 AE 1.5 years (5)(6)(7)(8)(9)(10)(11). Comparison of data at 2 years and at the last follow-up was also performed on these same patients.…”
Section: Populationmentioning
confidence: 99%
“…Denervation only temporarily improves pain without affecting joint mobility, grip strength, or radiological changes. [4][5][6][7] Studies on TWF and especially TWA have shown a decline in long-term survival, even when the preliminary results were favorable. Amandys is a pyrocarbon implant used as an interposition arthroplasty.…”
mentioning
confidence: 99%
“…De Kesel et al (2012) argued that resection of articular branches lead necessarily to a sensory or motor deficit. As is the case with denervation for chronic pain about the wrist (Chin et al, 2019), we posit that neurologic deficits can be avoided via selective resection of the nociceptive articular branches to the elbow joint.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…3 SWD can be performed by doing a posterior interosseous nerve (PIN) neurectomy or/and an anterior interosseous nerve (AIN) neurectomy. 4 , 5 One common complication of SWD is neuroma formation, which is an “inevitable and biologic response of the proximal stump after it has been divided in situations where regenerating axons are impeded from re-entering the distal stump.” 6 Several techniques have been suggested in the literature to prevent neuroma formation, including implantation of the nerve in a surrounding muscle or vein, neurorrhaphy, nerve stripping or silicone rubber capping. 7 Despite the existence of several approaches, no technique is recognized as the gold standard in the management of terminal neuromas.…”
Section: Introductionmentioning
confidence: 99%